Comparison of an interviewer-administered with an automated self-administered 24 h (ASA24) dietary recall in adolescents. Issue 17 (11th September 2017) - Hughes, Ashley R; Summer, Suzanne S; Ollberding, Nicholas J; Benken, Laura A; Kalkwarf, Heidi J
Abstract: Objective: The current pilot study aimed to assess whether reporting quality would decline materially in adolescents completing weekly web-based Automated Self-Administered 24-Hour dietary recalls (ASA24-Kids-2014) and interviewer-administered 24 h dietary recalls for six weeks. We also aimed to assess method preference. Design: We conducted two studies. Study 1 ( n 20) randomized participants to complete either one ASA24-Kids-2014 or one interviewer-administered recall weekly, for six weeks. Energy intake and number of foods reported were described for each method over time. Differences between recall methods for each measure were tested using mixed-effects regression. Study 2 ( n 10) employed a randomized crossover design to describe method preference. Setting: Dietary intake was collected either by telephone (interviewer-administered dietary recalls) or via the Internet (ASA24-Kids-2014 dietary recalls). Subjects: Adolescents aged 12–17 years with no prior diet recording experience were enrolled. Results: In Study 1, mean (sd ) total energy and number of foods reported decreased by 50 (222) kJ (12 (53) kcal) and 0·05 (0·31) items v . 38 (138) kJ (9 (33) kcal) and 0·17 (0·14) items per recall for participants randomized to the ASA24-Kids-2014 v . interviewer-administered recalls, respectively. There was no difference between groups for either measure ( P > 0·57). In Study 2, eight of ten participants preferred the interviewer-administered recall over the ASA24-Kids-2014. Overall, seven of twenty participants experienced technical difficulties with the ASA24-Kids-2014. Conclusions: No appreciable decay in reporting quality was seen for either method. However, participants reported a preference for the interviewer-administered recall. Our findings can help inform and support larger studies to further characterize the performance of the ASA24 in adolescents.